Impact of timing of randomization after an acute coronary syndrome and subsequent events in patients with type 2 diabetes mellitus: an analysis of the EXAMINE trial. (25th November 2020) - Elharram, M; Sharma, A; White, W; Bakris, G; Rossignol, P; Mehta, C; Ferreira, J; Zannad, F
Abstract: Background: The timing of enrolment following an acute coronary syndrome (ACS) may influence cardiovascular (CV) outcomes and potentially treatment effect in clinical trials. Using a large contemporary trial in patients with type 2 diabetes mellitus (T2DM) post-ACS, we examined the impact of timing of enrolment on subsequent CV outcomes. Methods: EXAMINE was a randomized trial of alogliptin versus placebo in 5380 patients with T2DM and a recent ACS. The primary outcome was a composite of CV death, non-fatal myocardial infarction [MI], or non-fatal stroke. The median follow-up was 18 months. In this post hoc analysis, we examined the occurrence of subsequent CV events by timing of enrollment divided by tertiles of time from ACS to randomization: 8–34, 35–56, and 57–141 days. Results: Patients randomized early (compared to the latest times) had less comorbidities at baseline including a history of heart failure (HF; 24.7% vs. 33.0%), prior coronary artery bypass graft (9.6% vs. 15.9%), or atrial fibrillation (5.9% vs. 9.4%). Despite the reduced comorbidity burden, the risk of the primary outcome was highest in patients randomized early compared to the latest time (adjusted hazard ratio [aHR] 1.47; 95% CI 1.21–1.74) (Figure 1). Similarly, patients randomized early had an increased risk of recurrent MI (aHR 1.51; 95% CI 1.17–1.96) and HF hospitalization (1.49; 95% CI 1.05–2.10). Conclusion: In a contemporary cohort of T2DM with a recent ACS, early randomization following the ACS increases the risk of CV events including recurrent MI and HF hospitalization. This should be taken into account when designing future clinical trials. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Takeda Pharmaceutical